Urban Experience in Kathmandu: Alienation and Social Fragmentation in Khanal’s Pashupati Prasad - Dumre, Mani Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Kathmandu is growing fast. The city now exhibits sharp class divisions, crowded streets, and a growing sense of anonymity. These changes invite an urban‑sociological look.Methods: This study applies Louis Wirth's concept that urbanism leads to social fragmentation and impersonality, alongside Georg Simmel's view that metropolitan life fosters psychological distancing and heightened individualism, to analyze key scenes, characters, and settings in Pashupati Prasad (2016).Result: The film exemplifies several of Wirth’s urban characteristics, including weakened social bonds, pronounced class divisions, and impersonal interactions. Through the protagonist’s experiences, the narrative reveals adaptive social strategies amid pervasive alienation, thereby contextualizing Western urban sociological theories within the specific socio-cultural realities of Kathmandu.Conclusion: The film illustrates how rapid urban change can weaken old bonds while forcing new ways of coping in the city.Novelty: The film's narrative, characters, and urban setting reveal nuanced portrayals of alienation, social fragmentation, and adaptive strategies within Nepal’s rapidly transforming capital cityscape today.